Drug research and development opportunities in low- and middle-income countries: accelerating traditional medicine through systematic utilization and comprehensive synergy - Guangqi Liu; Yan Xie; Yinuo Sun; Kaixuan Zhang; Jiyan Ma; Yangmu Huang (BMC, 2022)
Abstract Background Though the utilization of traditional medicine has been proposed for modern drug research and development (R&D), limited research has discussed its feasible paths. In this commentary, we summarized key factors for new drug R&D under limited resources by reviewing China's discovery of artemisinin, and raised suggestions to utilize traditional medicines in low- and middle-income countries (LMICs). Main text We suggested that systematic utilization of traditional medicine, outstanding synergy of research units at all levels and timely information-sharing mechanism should be achieved to establish a comprehensive and efficient R&D system, especially under low-resource settings. In the case of artemisinin discovery, Chinese scientists integrated documented traditional medicine experiences and modern approaches to develop drug candidates timely. Due to limited R&D resources, China adopted a collaborative way, motivating nearly all domestic research units at different levels, to develop antimalarial products. Moreover, the excellent synergy among all units through efficient information-sharing mechanisms greatly avoided work repetition and accelerated the R&D process. Conclusion Traditional medicines inspires drug discoveries in LMICs, while a comprehensive and efficient R&D system could accelerate its R&D process and save investment. The discovery of artemisinin in China gave a reliable pattern to promote sustainable development of traditional medicines and a good example to realize R&D of traditional medicine under low-resource settings.